2014
DOI: 10.1111/soc4.12186
|View full text |Cite
|
Sign up to set email alerts
|

Nation in Market Times: Connecting the National and the Commercial. A Research Overview

Abstract: This article provides an overview of the growing body of research pertaining to different forms of mediated nationhood. In particular, it focuses on the relatively recent trend toward increasing articulations of national identity with the language of consumerism and neoliberal market ideology. It argues that the process is twofold; on the one hand commercial entities employ nationalist appeals in order to sell their commodities, a process which is called “nationalizing the commercial”. On the other hand, natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…While initially developed in relation to state-led initiatives, nation branding has rapidly evolved into a process that ties together a wide range of both political and commercial actors. In this sense, as Kania-Lundholm (2014) notes, a dual process is at work that involves a simultaneous nationalization of the commercial and the commercialization of the national; on the one hand, commercial entities use nationalism to sell goods and services, while states use marketing techniques to develop successful nation brands. This dual process is at the heart of what Volčič and Andrejevic (2015) refer to as ‘commercial nationalism’, a term designed to encompass a broad range of phenomena that emerge when states and societies start envisioning themselves as corporations built to turn profit from their national culture.…”
Section: Mapping the Fieldmentioning
confidence: 99%
“…While initially developed in relation to state-led initiatives, nation branding has rapidly evolved into a process that ties together a wide range of both political and commercial actors. In this sense, as Kania-Lundholm (2014) notes, a dual process is at work that involves a simultaneous nationalization of the commercial and the commercialization of the national; on the one hand, commercial entities use nationalism to sell goods and services, while states use marketing techniques to develop successful nation brands. This dual process is at the heart of what Volčič and Andrejevic (2015) refer to as ‘commercial nationalism’, a term designed to encompass a broad range of phenomena that emerge when states and societies start envisioning themselves as corporations built to turn profit from their national culture.…”
Section: Mapping the Fieldmentioning
confidence: 99%
“…The ‘process of economization of the social’ thus takes over the ‘articulation and communication of nationhood’ (Kania‐Lundholm : 611). Nationalism sheds its darkness, turning into a means of naming, locating or explicating.…”
Section: Discussionmentioning
confidence: 99%
“…Via slogans, logos and an array of promotional materials creating a unitary visual representation, nation‐branding campaigns attempted to fix the meaning of nations in simplistic and light‐hearted ways. Furthermore, in becoming increasingly involved in the selling of products and services (Kania‐Lundholm ), the nation turned into the promise of a competitive advantage in a global marketplace (Aronczyk ). Overall, these practices ‘privilege the economic route to nationalism, meaning nationalism is increasingly reproduced by means of institutions and practices attached to the economic realm’ (Castelló and Mihelj : 6).…”
Section: The Question Of Ideological Reproduction: From Official To Bmentioning
confidence: 99%
“…Food, food writing, food production, food distribution, food consumption and food promotion are intrinsic parts of everyday lives (DeSoucey, 2010;Ferguson, 2010;Kania-Lundholm, 2014;Palmer, 1998). Research has long established how food products are branded to create differentiation and nature and nationalism have been an important part of this process (see for example Ichijo & Ranta, 2016).…”
Section: Food Promotion Banal Nationalism and Naturementioning
confidence: 99%
“…Since the 1990s the promotion of food products as 'national' has increased (Aronczyk, 2008;Ichijo & Ranta, 2016) also a form of banal nationalism. Nations and their symbols are used in the discourse of 'corporate nationalism' as a means to link a brand to a national identity, and thus re-imagining, representing and reproducing the nation (Kania-Lundholm, 2014;Prideaux, 2009). Research has also shown that food can be promoted using appeals to nationalist associations of landscape and national pride (see for example Ichijo & Ranta, 2016).…”
Section: Introductionmentioning
confidence: 99%